Challenges Facing Women in School Leadership Positions: At Community Schools in Lalitpur Nepal - Ghimire, Durga Devi (Pragyaratna प्रज्ञारत्न, 2023)
Women's leadership in education, particularly in the role of women head teachers, plays a pivotal role in advocating for women's rights and fostering inclusive development. However, women in school leadership positions encounter substantial obstacles stemming from cultural, economic, and social factors. This study's primary objective is to delve into the perceptions and experiences of women headteachers concerning the multifaceted challenges they confront while leading community schools in the Lalitpur district of Nepal. To accomplish this, in-depth interviews will be conducted with three women head teachers representing different community schools. Despite the evolving landscape, Nepal still grapples with the prevailing perception of women as second-class citizens. Furthermore, state laws have not entirely rectified these societal disparities, particularly within educational leadership roles. In many instances, women in school leadership positions do not receive the encouragement they deserve, and they often face bias, where they are seen as inferior to their male counterparts. The complex challenges and disparities faced by women in educational leadership underscore the need for further research to comprehensively understand the issue, given the potential diversity of perspectives within Nepalese society.